PERLINDUNGAN HUKUM TERHADAP INVESTASI ASING YANG MASUK DI PROVINSI RIAU - Lysa Angrayni (Universitas Islam Negeri sultan syarif kasim Riau, 2019)
Law Number 25 Year 2007 concerning Capital Investment gives equal treatment to Domestic Investment and foreign investors with due regard to the national interest, ensures legal certainty, and security of business for investors since the process of licensing until the end of investment activities in accordance with the provisions of legislation. Under the Act it is clear that foreign investors must obtain legal protection and certainty as domestic investors. But the reality is different so the impact that arises that uncertainty is the development of unstable foreign investment, a significant increase and decrease in Riau Province. While the factors causing the decline of foreign investment in Riau Province are the differences in both licensing, raw materials and protection between foreign investors and domestic investors in Riau Province, so foreign investors feel unsafe to invest in Riau Province.